Dark Triad Personality as Predictor of Corrupt Intention on the State Civil Apparatus - Widya Wijaya Kusuma Putri; Yusti Probowati Rahayu; Ajuni Arunima (Journal of Educational, Health and Community Psychology, 2021)
Referring to the theory of planned behavior, behavior appear because of behavior intention, where personality was one of behavior intention’s factor. The aims of this study was to examine the correlation between dark triad personality and corrupt intention in government employees. Data were collected using accidental sampling with cross-sectional survey quantitative research design on 75 government employees from four different sub-district. The result showed that there was a significant positive correlation between dark triad personality and corrupt intention (r=0,415; p=0,001). Additional analysis showed that corruption is a crime caused of weak regulation system and supervision (PBC r=0,665). Last but not least, dark triad personality’s aspect narcissism was the most influenced of corrupt intention (r=0,413). The theoretical implication found in this study was, dark triad personality is nit direct predictor of corrupt intention, but an indirect predictor through attitude towards behavior, subjective norms, and perceived behavior control.